2017
DOI: 10.1038/srep45898
|View full text |Cite
|
Sign up to set email alerts
|

Artificial spatiotemporal touch inputs reveal complementary decoding in neocortical neurons

Abstract: Investigations of the mechanisms of touch perception and decoding has been hampered by difficulties in achieving invariant patterns of skin sensor activation. To obtain reproducible spatiotemporal patterns of activation of sensory afferents, we used an artificial fingertip equipped with an array of neuromorphic sensors. The artificial fingertip was used to transduce real-world haptic stimuli into spatiotemporal patterns of spikes. These spike patterns were delivered to the skin afferents of the second digit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
106
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(127 citation statements)
references
References 61 publications
13
106
1
Order By: Relevance
“…Note that we have previously reported that there is no relationship between recording depth and decoding of the tactile afferent inputs we used (Oddo et al . ). The ECoG electrode was placed at the rostral end of the craniotomy.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Note that we have previously reported that there is no relationship between recording depth and decoding of the tactile afferent inputs we used (Oddo et al . ). The ECoG electrode was placed at the rostral end of the craniotomy.…”
Section: Methodsmentioning
confidence: 97%
“…the same approach as reported in a previous study (Oddo et al . ). For each skin site the stimulation pulse was set to an intensity of 0.5 mA with a duration of 0.14 ms (DS3 Isolated Stimulator, Digitimer, Welwyn Garden City, UK), which is 2.5 times the threshold for activating tactile afferents (Rasmusson & Northgrave, ; Bengtsson et al .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations